Repeated oral ketamine for out-patient treatment of resistant depression: randomised, double-blind, placebo-controlled, proof-of-concept study. (24th September 2018) - Domany, Yoav; Bleich-Cohen, Maya; Tarrasch, Ricardo; Meidan, Roi; Litvak-Lazar, Olga; Stoppleman, Nadav; Schreiber, Shaul; Bloch, Miki; Hendler, Talma; Sharon, Haggai
Abstract : Background: Ketamine has been demonstrated to improve depressive symptoms. Aims: Evaluation of efficacy, safety and feasibility of repeated oral ketamine for out-patients with treatment-resistant depression (TRD). Method: In a randomised, double-blind, placebo-controlled, proof-of-concept trial, 41 participants received either 1 mg/kg oral ketamine or placebo thrice weekly for 21 days (ClinicalTrials.gov Identifier: NCT02037503). Evaluation was performed at baseline, 40 and 240 min post administration and on days 3, 7, 14 and 21. The main outcome measure was change in Montgomery–Åsberg Depression Rating Scale (MADRS). Results: Twenty-two participants were randomised to the ketamine group, and 19 to the control, with 82.5% ( n = 33) completing the study. In the ketamine group, a decrease in depressive symptoms was evident at all time points, whereas in the control group a decrease was evident only 40 min post administration. The reduction in MADRS score on day 21 was 12.75 in the ketamine group versus 2.49 points with placebo ( P < 0.001). Six participants in the ketamine group (27.3%) achieved remission compared with none of the controls ( P < 0.05). The number needed to treat for remission was 3.7. Side-effects were mild and transient. Conclusions: Repeated oral ketamine produced rapid and persistent amelioration of depressive symptoms in out-patients with TRD, and was well tolerated. These results suggest that add-on oral ketamine may hold significant promise in the care of patients suffering from TRD in the community. Declaration of interest: None.